Tropical Legumes in Animal Nutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Edited by PJF D'Mello, Scottish Agricultural College, Edinburgh, UK, and CC Devendra, International Development Research Centre, Singapore / CABI. 352 pp.ISBN 0851989268CTA number 940. 80 credit points.